The Concept of Brotherhood in Islam: Overcoming Social Challenges and Building Tolerance - Abdul Halim; Bahaking Rama; M. Ilham Muchtar (Annujum: Journal of Humaniora and Law, 2025)
The concept of ukhuwah (brotherhood) in Islam is a fundamental value that teaches the importance of brotherhood, solidarity, and harmony among humanity. Broadly speaking, ukhuwah is divided into several types: ukhuwah insaniyah (human brotherhood), ukhuwah Islamiyah (brotherhood among Muslims), ukhuwah wathaniyah (national brotherhood), and ukhuwah manusiaiyah (brotherhood among all creatures). Each of these types of ukhuwah has basic principles that lead to the formation of harmonious and mutually supportive social relationships within society. However, in this modern era full of challenges, the values of ukhuwah face various challenges, such as the emergence of divisions and conflicts between Muslims, between religions, and between ethnic groups. This article will also discuss the application of the principle of ukhuwah in addressing contemporary issues, such as increasing solidarity, tolerance, and harmony in a multicultural society. The application of the principle of ukhuwah is expected to be a solution to improve social relations amidst existing differences, create peace, and strengthen a sense of unity and oneness in an increasingly pluralistic global society.